Collaborative Model in Teaching Linguistics (A Grounded Theory Study at Universitas Borneo Tarakan) - Rafiqa, Syarifa; Vega, Nofvia De (Universitas Muhammadiyah Mataram, 2024)
This study looks into collaborative techniques in linguistics education, focusing on fundamental concepts, principles, components, and the roles of many stakeholders in the educational process. The study demonstrates how collaborative models can improve linguistics education by ensuring active involvement and social interaction between students and teachers. This study employs a grounded theory methodology, which includes qualitative data gathering and analytical techniques, such as open, axial, and selective coding, to discover main themes and patterns. The interviews and discussions with professors and students from the English and Indonesian language departments are included in the research design, allowing for a thorough examination of their experiences and perspectives. Micro-linguistic theory, communicative skills, and collaborative techniques are essential to good linguistics teaching. Key findings suggest that when approaches are employed, and there is more activity, linguistic competency increases, and general educational outcomes improve. The findings spark curiosity about the role of instructor mediation, classroom management, and multimedia resources in improving collaboration. This study's outcomes suggest potential routes for future research on collaborative strategies in linguistics education, particularly with the use of technology and multimedia learning systems. Further research is needed to investigate the long-term effects of these strategies on student accomplishment and the viability of these models in various educational contexts.